2007
DOI: 10.4049/jimmunol.179.12.8083
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of NF-κB Activation in Lymphocytes Prevents T Cell Apoptosis and Improves Survival in Murine Sepsis

Abstract: Sepsis induces extensive lymphocyte apoptosis that contributes to immunosuppression and mortality. Activation of the canonical NF-κB pathway, however, prevents TNF-α–induced lymphocyte apoptosis. In this study the function of canonical NF-κB in T cells was studied in the context of murine sepsis. Upon cecal ligation and puncture (CLP), NF-κB DNA binding activity in thymocytes declines relative to sham-operated mice. This decline in NF-κB activity is most likely due to posttranslational modifications such as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Getts et al recently demonstrated that inflammatory monocytes undergo apoptosis in the spleen with the sodium thioglycollate (TG) peritoneal inflammation mouse model of colitis [38]. Even in CLP sepsis model, methods that interfere with the progress of apoptosis have been demonstrated to prevent cell apoptosis and protect against polymicrobial endotoxic shock, further indicating that apoptosis promotes the induction of sepsis [39,40]. In the current study, we observed that TLR9 ablation prevented apoptosis in the spleen after CLP as demonstrated by decreased percent of TUNEL-positive cells, lowered expression levels of cleaved caspase-3 and Bax, but increased Bcl-2 protein when compared to WT littermates.…”
Section: Discussionmentioning
confidence: 99%
“…Getts et al recently demonstrated that inflammatory monocytes undergo apoptosis in the spleen with the sodium thioglycollate (TG) peritoneal inflammation mouse model of colitis [38]. Even in CLP sepsis model, methods that interfere with the progress of apoptosis have been demonstrated to prevent cell apoptosis and protect against polymicrobial endotoxic shock, further indicating that apoptosis promotes the induction of sepsis [39,40]. In the current study, we observed that TLR9 ablation prevented apoptosis in the spleen after CLP as demonstrated by decreased percent of TUNEL-positive cells, lowered expression levels of cleaved caspase-3 and Bax, but increased Bcl-2 protein when compared to WT littermates.…”
Section: Discussionmentioning
confidence: 99%
“…Still, in our patients IL-6 could not maintain the levels of Bcl-2 and Bcl-xl. Another mechanism for the downregulation of Bcl-2 and Bcl-xl in sepsis has been described recently by Groesdonk and colleagues [ 38 ]. It was shown that the DNA-binding activity of nuclear factor kB was reduced in T-cells of septic mice; however, sufficient expression of these anti-apoptotic proteins is dependent on the canonical activation of nuclear factor kB.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis-related mortality results in part from immunodeficiency secondary to profound lymphoid apoptosis (1,2,(27)(28)(29)(30). The biological mechanisms responsible for this extensive lymphocyte cell death are not understood but have been attributed in part to direct pathogen signaling through toll-like receptors and MyD88 (31).…”
Section: Discussionmentioning
confidence: 99%